Captagon: A comprehensive bibliometric analysis (1962-2024) of its global impact, health and mortality risks - Seraphina Fong; Alessandro Carollo; Andrea Rossato; Elisabeth Prevete; Gianluca Esposito; Ornella Corazza (Elsevier, 2024)
Captagon is a synthetic stimulant combining amphetamine and theophylline. Initially introduced in 1961 as a treatment for hyperactivity, depression, and narcolepsy, Captagon was later classified as a Schedule 1 controlled substance due to its addictive and hallucinogenic properties. Despite its global prohibition in 1986, the trade of counterfeit products is widespread, especially in south-east Europe and far-east Asia, with its production being on the rise in Middle Eastern regions. This paper presents a quantitative data-driven bibliometric analysis of the existing literature on Captagon up to July 2024. It aims to delineate the structure and development of knowledge surrounding the substance, including key contributing countries, authors, prominent sources, and recurring thematic keywords. The quantitative and data-driven results were then used to guide the narrative discussion on Captagon. Findings indicate that current research predominantly focuses on Captagon's use and impact in conflict zones, often exploring its interaction with other substances used by civilians and militias. Results also show a growing trend in Captagon research, with Saudi Arabia, Jordan, and Iraq emerging as main contributors to the literature. Despite the attention in specific regions, a considerable gap remains in understanding the mechanisms of action of Captagon (particularly regarding its metabolism, toxicology, mortality risk), and in developing protocols for its discontinuation. Additionally, the drug's inconsistent composition requires further analyses to better predict risks and establish effective management strategies. Addressing these gaps will be crucial for the development of novel interventions and policies to mitigate the adverse effects of Captagon and improve public health systems worldwide.